Actors, fornicators, and other transgressors of law. Issue 2 (3rd July 2021) - Raffield, Paul
ABSTRACT: It is the purpose of this article to examine the treatment of actors (and other 'outlaws') by the state in the late Elizabethan and early Jacobean period, with the intention of exploring the general theme of 'otherness' and the particular role of the legal institution in regulating and reforming the image of the citizen or subject of law in post-Reformation, English society. I refer throughout to seminal, primary sources on the subject (especially) of theatre. I draw on several contemporaneous, polemical works (notably The Schoole of Abuse by Stephen Gosson and The Anatomie of Abuses by Phillip Stubbes), most of which demonstrate an iconoclastic attitude towards the theatrical image, consonant with devout Protestant opposition to idolatry. In the second half of the article, I examine prevailing and pressing concerns surrounding plague and disease, which I interpret as metaphors for a diseased and decaying society, in urgent need of reform. I make extensive reference here to Shakespeare's Measure for Measure, and its thinly veiled allusions to the social and political ills of Jacobean society. I conclude with the observation that Shakespeare's Vienna provides a depiction of an ossified state, in which the plight of the underprivileged, the poor, and the oppressed is ignored by an autocratic and self-serving ruler. The parallels with Jacobean society and its magistracy are compelling.